Diversity of Orchids in Tahura Nuraksa Central Lombok as Enrichment of Biodiversity Subject - Dita Anggraini Safitri Sipayung; Didik Santoso; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This study was done to determine the diversity of orchid species, population structure (abundance, diversity, dominance and distribution patterns) of orchids found in the Tahura Nuraksa and to make a booklet as enrichment of biodiversity courses. The research was conducted at the Tahura Nuraksa Resort, Kalipalang, Central Lombok. The method used in this study was descriptive exploratory by determining the location of observation using purposive sampling method and sampling by using non-destructive and exploratory methods. The results showed that there were 544 individuals from 18 species of orchid . An abundance of orchids of 1% was in the low category, and the dominance of orchids is 0,15% which means that there was a dominant species of orchids, namely Spathoglottis plicata. The orchids diversity index was 2.25 (medium category) and the distribution pattern of orchids in the study sites was generally uniform. The booklet is declared worthy of being an enrichment for study of biodiversity.